Indonesia Islamic Banking Readiness in Facing the ASEAN Economic Community 2015, in terms of Islamic Banking Disclosure and Performance Indices - Zaina, Veithzal Rivai; Putra, Bobby Yulandika (Online Journal of Research in Islamic Studies, 2016)
This research is aimed to analyze the level of openness of Indonesia Islamic Banking which is viewed from Islamic Banking Disclosure Index based on Sharia Compliance Indicator, Corporate Governance Indicator and Social/Environment Indicator, analyze the financial performance of Indonesia Islamic Banking which is viewed from Islamic Banking Performance Index during 2008 Ã‚â€“ 2013, as well as to analyze and/ or propose policies to the regulator, the Financial Services Authority (OJK) and Bank Indonesia (BI) related to the readiness of the Islamic banking in facing of AEC 2015, particularly in terms of disclosure and performance. This research used the quantitative and qualitative methods. The use of quantitative method in this research looks at the evaluation of Islamic Banking Performance Index, where the researchers process secondary data from Islamic Bank in Indonesia to get financial ratios and in the end it will produce output Islamic Banking Performance Index. The use of qualitative method in this research looks at the evaluation of Islamic Banking Disclosure Index, where the researchers analyze and process the data . This output would produce Islamic Banking Disclosure Index. The result of this research shows Islamic Banking Disclosure Index of Indonesia Islamic Banking (82.71%) higher than ASEAN Islamic Banking (52.40%). It can be concluded that Indonesia Islamic Banking more open to reveal the information / publication related to Sharia Compliance Indicator, Corporate Governance Indicator and Social/ Environment Indicator. Based on the analysis of Islamic Banking Performance Index, it is concluded that Indonesia Islamic Banking better and more stable, which the analysis value is not relatively different than ASEAN Islamic Banking.